ANALISIS FAKTOR FAKTOR YANG BERPENGARUH TERHADAP KEBERHASILAN USAHA MIKRO DAN KECIL ( Studi Pada Usaha Kecil Di Semarang Barat) - Indriyatni, Lies (Sekolah Tinggi Ilmu Ekonomi Semarang, 2013)
This research aimed on analyzing factors which influenced the success of micro and small business in West Semarang (Semarang Barat) region. The research had been done by picking 100 sample of micro and small business in West Semarang region. Data collecting was achieved through Interview and Questioners. Next, the data was being processed using SPSS ver.16. The result showed that working fund, skills, and business  location  have  positive  and  significant influence  on  the  achievement  of micro and small business to gain some benefits by the significant points for each factors are 0.002; 0.0015 and 0.003 while the Adjusted R Square is 0.348 or 34.8%. Between those three factors, work location is the most influencing factor with beta coefficient 0.24.  The result also showed that there are some other factors (65.2%) which also have influence on the success of micro and small business but those factors wouldn’t be researched here.